Alimentación de los peces dulceacuícolas tropicales Heterandria bimaculatayPoecilia sphenops (Cyprinidontiformes: Poeciliidae) - Trujillo Jiménez, Patricia (2007)
We analyzed the diet and feeding habits of the fishes Heterandria bimaculata and Poecilia sphenops. Specimens were captured monthly in “Los Carros” damp, Morelos, Mexico (18°37 ́ N, 98°43 ́ W). We quantified gut content by the numerical method and by the fre-quency of occurrence method; and used the MacArthur and Levin ́s indices for niche overlap. The diet of H. bimaculata was composed by 16 prey categories, mainly dipterans (Culicidae predominated), independently of sex, size and season. The index of niche overlap was high, from 0.74 to 0.99. The diet of P. sphenops consisted of 11 items, detritus being the most consumed, also independently of sex, size and season. The niche overlap index was high (0.99), indicating overlapping for all analyses. There was little diet overlap (0.26) between the two species.